Antarctic close-up - Edwards, Hazel; Parkee, Meegan (Canberra ACT : National Museum of Australia Press, 2007)
John likes to tinker with things and when he connects a broken webcam with an old telescope his father has at his auction house, John can see into the past when another person name John was exploring Antarctica.
3.6
K-3.
K-3
Keywords: Science fiction; Science fiction; Antarctica -- Juvenile fiction; Antarctica -- Discovery and exploration -- Juvenile fiction; Antarctica; Antarctica -- Discovery and exploration; Antarctica; Antarctica -- Exploration; Science fiction